Cartografia regional da leptospirose: dinâmica espaço-temporal da patologia na 4ª Coordenadoria Regional de Saúde, RS. - Schmitz, Carlos André Aita (2010)
Leptospirosis is a ubiquitous disease, waterborne, with several animal reservoirs (wild and domestic) and urban and rural transmission, receiving climatic/socioeconomic influences. Its manifestations vary from asymptomatic and light tables to hemorrhagic fevers. This study aimed to evaluate the cases reported in SINAN of the 4ªCRS, RS, from 1999 to 2006, performing the spatialization of regional events and looking for correlations with socioeconomic and environmental factors on a regional scale (rural occurrences/4ªCRS) and local scale (urban cases/Santa Maria). It was decided, in the first step, by a descriptive study design type investigation of a case series, to evaluate the completeness and description of the variables the investigation form and, in the second stage, in an ecological study design, exploring regional and local geographical comparisons, local geographical comparisons and local comparisons of chronological series. The regional events (131 rural cases) were compared with demographic, geographic and anthropogenic variables (agricultural/livestock production, population density and altitude of the municipal seat). In local geographical comparisons were used cases of urban infection in home environment (63 cases/Santa Maria), located on field survey and with the help of a digital cartographic base of the streets overlaid by census grid. It was considered the proportion of improvised households, not connected to the mains water supply, no toilet or with irregular sanitation, with irregular disposal of the trash, the proportion of illiterate people and population density. In the chronological series comparison were used the rainfall, the dues of the rivers that drain the city and the variables temperature and relative humidity. Statistical analysis was based on linear regression and Poisson regression with robust variance. Middle-aged adults (51.84%), males (68.66%) and people with low education (58.26%) were most affected. Activities related to agriculture (27.14%), and domestic activities (12.38%) were present in most cases. The percentages of 55.84 and 45.18 were involved, respectively, with animal husbandry and farming. The rural area has been implicated in most situations (48.34%). Primary care units centralizing many notifications (mild cases). Moreover, jaundice, myalgia and conjunctival congestion present significant differences between cases reported and confirmed, suggesting the hypothesis that this triad can be used for differential diagnosis. Similarly, changes in the kidneys, lungs and heart were observed in most of the deaths. The mean incidence (per 105 inhabitants) and cumulative mortality (%) were respectively 11.61 and 4.72 to Santa Maria and 9.81 and 3.23 for the regional and 5.17 and 5.52 to the state and 1.80 and 9.57 for the country. In regional study, statistical analysis and mapping of cases showed a trend (p <0.181) correlation to the occurrence of cases with altitude and a correlation with the herd pig (p <0.037). The local study found a correlation with population density (p <0.035) and the proportion of illiterate people (p <0.067). The proportion of households not connected to the water supply showed a trend correlation (p <0.187). In comparisons of chronological series, rainfall showed significant correlation (p> 0.053) and temperature showed a trend correlation (p <0.180) with the occurrence of urban cases. The data indicate the need for more investment in education and sanitation and raise the possibility of deepening the questions raised about the herd of pigs, the symptoms and the occurrence of urban cases.